2011
DOI: 10.1111/j.1755-6686.2011.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Egg Whites for Phosphorus Control in Maintenance Haemodialysis Patients: A Pilot Study

Abstract: SUMMARY Background High dietary protein intake is associated with greater survival in maintenance haemodialysis (MHD) patients. High-protein foods may increase dietary phosphorus burden, which is associated with increased mortality in these patients. Hypothesis is: an egg white based diet with low phosphorus to protein ratio (<1.4 mg/g) will lower serum phosphorus without deteriorating the nutritional status in MHD patients. Objective We assessed serum phosphorus and albumin levels in MHD patients who agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 50 publications
0
27
2
2
Order By: Relevance
“…Moreover, among animal sources, the proportion of phosphate bioavailability varies greatly. While meat is generally highly digestible and offers high relative bioavailability, red meat and fish contain more phosphate than poultry [152]. Interestingly, the phosphate content in dairy products is variable, with differing phosphate bioavailability across dairy food types (milk vs. cheese) and even within the same class, for example, low-fat vs. whole milk [14].…”
Section: Animal-based Phosphatementioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, among animal sources, the proportion of phosphate bioavailability varies greatly. While meat is generally highly digestible and offers high relative bioavailability, red meat and fish contain more phosphate than poultry [152]. Interestingly, the phosphate content in dairy products is variable, with differing phosphate bioavailability across dairy food types (milk vs. cheese) and even within the same class, for example, low-fat vs. whole milk [14].…”
Section: Animal-based Phosphatementioning
confidence: 96%
“…Interestingly, the phosphate content in dairy products is variable, with differing phosphate bioavailability across dairy food types (milk vs. cheese) and even within the same class, for example, low-fat vs. whole milk [14]. Further, whole eggs, including the yolk, contain more phosphate than egg whites: one large whole egg contains 6 g of protein and 86 mg of phosphate, whereas an egg white from one large egg contains 4 g of protein and only 5 mg of phosphate [152]. This is one important example of how dietary phosphate and protein can be dissociated, which has important implications for patients undergoing dialysis in whom high protein intake is desirable but must be balanced by avoiding excessive phosphate loading.…”
Section: Animal-based Phosphatementioning
confidence: 97%
“…Inorganic phosphorus is present in processed-food additives,11 which are highly absorbable, and is highly abundant in the diet of postmodern industrialized regions 14. Organic phosphorus is found in animal- and plant-derived protein-rich foods; however, the phosphorus-to-protein ratio differs markedly depending on the food source 15. Although plant proteins also contain phosphorus, much plant phosphorus is in the form of less-absorbable phytates 13.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, two pilot studies have shown promising effects of nutritional supplementation on serum albumin. In one study, maintenance HP consumed eight ounces of egg whites (egg whites are low in phosphorus) once per day for six weeks (Taylor, et al, 2011). Mean serum albumin concentrations increased by 0.19 g/dL along with a fall in mean serum phosphorus of 0.94 mg/dL.…”
Section: Nutritional Supplementation and Hemodialysis Patientsmentioning
confidence: 99%
“…Recently, studies have investigated the effects of protein and amino acid supplements on serum albumin levels in HP (Bolasco, Caria, Cupisti, Secci, & Saverio Dioguardi, 2011;Moretti, Johnson, & Keeling-Hathaway, 2009;Taylor et al, 2011). When selecting an appropriate nutritional supplement for HP, phosphorus levels must be taken into consideration as it has been demonstrated that high-protein intake with concurrent lowphosphorus ingestion and normal serum phosphorus levels is associated with the lowest mortality rate among HP (Kalantar-Zadeh et al, 2010).…”
Section: Nutritional Supplementation and Hemodialysis Patientsmentioning
confidence: 99%